If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 6 = 10 + -1n Reorder the terms: 6 + 3n = 10 + -1n Solving 6 + 3n = 10 + -1n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add 'n' to each side of the equation. 6 + 3n + n = 10 + -1n + n Combine like terms: 3n + n = 4n 6 + 4n = 10 + -1n + n Combine like terms: -1n + n = 0 6 + 4n = 10 + 0 6 + 4n = 10 Add '-6' to each side of the equation. 6 + -6 + 4n = 10 + -6 Combine like terms: 6 + -6 = 0 0 + 4n = 10 + -6 4n = 10 + -6 Combine like terms: 10 + -6 = 4 4n = 4 Divide each side by '4'. n = 1 Simplifying n = 1
| a+4b=-4 | | -4+4x=3x+2 | | -4.7=g/-3.2 | | -3x+4=-4x+1 | | X^2-6y+8=0 | | 2x-7=13-3x | | -10(x-5)+76=-12-12 | | 3/2n-7/2n=7/2 | | y=0*ln(0) | | 3+x=X+2 | | 7/9-3a=17 | | -7(2t+1)=49 | | 8y-13y=26-34 | | t^2-6t-14=0 | | 4(f-5)=-40 | | 4x^2+5(9)-20=0 | | 3x-1y+8=0 | | 4ln(4x)=20 | | -7a=-56 | | 39=13/10b | | x=y/2 | | 4x^2+5(2)-20=0 | | 7y=16x-3 | | 4(2y+5)=3(5y-2) | | 26x^2+18x= | | 2*3x-4-1*2x+1=1*2 | | 552.50=.0015x | | 10(s-8)=-169 | | 5y+5=18 | | 1x-4y+5=0 | | (5x^3)-(4x^2)+90x-8=0 | | 27-7x=24 |